THE SHADOW BANKING SYSTEM - Giudice Baca, Víctor Manuel (2016)
The shadow banking system is an emerging financial sector with large funds that compete with the Banking System, such as AFPs, Cooperatives, Consumer Banking, Credit Cards, Stock Brokerage Firm (SBF), Mutual Funds, Municipal Banks credit, CRAC, and in developed countries large consulting firms turned into sources of financing and securities issue. The US Shadow Banking system already owns 36% of the total assets of the Banking System, in the eurozone a 39%, in Peru it grows out of the regulation of the supervisory authorities. Shadow Banking System emerged in developed countries due to over-regulation of the Banking System, the lack of coverage of inflation on bank deposits interest rates, the quicker technological change than the formal Banking System; the strong attraction of managers and qualified personnel from the Banking System towards the Shadow Banking System. It is composed of institutions beginning to settle transactions among themselves: AFPs obtain bonus and securities from the SBFs; AFPs buy insurance policies; AFPs increase (leverage) the Operating Funds from the formal Banking System. Foreign banks consumer credit - Saga Falabella already has six million credit cards in the international market, Banco Azteca and Microcredit NGOs add to the emerging sector of Shadow Banking System.